PENGARUH CONTEXTUAL TEACHING AND LEARNING TERHADAP HIGHER ORDER THINKING SKILLS GEOMETRI BANGUN RUANG - Dita Alvinda Calista; Rusijono Rusijono; Utari Dewi (Akademika, 2022)
This study aims to determine the effect of contextual teaching and learning onhigher-order thinking skills in geometry. Geometry is one of the scopes of mathematics, inwhich it studies lines, spaces, and volumes that are abstract and related to each other,have lines and points so that they become symbols such as squares, triangles, circles,and others, the method used is a quasi-experimental design with 60 high school studentsas research subjects, divided into two groups experimental and control. There are threecomponents of higher-order thinking skills in this study, 1) creative thinking, 2) logicalthinking, and 3) problem-solving. the three components were measured using a test. Dataanalysis technique by comparing the two groups that were tested statistically. Statisticaltest results obtained sig. 0.68 > 0.05 can be concluded that CTL has a significant effecton the ability of HOTS in geometry